The Influence of Sit-Up and Squat-Jump Practice on Football Leading Results in Class VIII Students of SMP Negeri 8 Watampone - Muzakkir; Andi Ogo Darminto; Umrah Bahar; Adli Azhari (International Journal of Educational and Psychological Sciences, 2023)
The purpose of this study was to find out the effect of sit-up and squat-jump exercises on the results of heading soccer games for class VIII male students of SMP Negeri 8 Watampone. This research was a quasi-experimental study with a "pre-test and post-test group design. The instrument in this study was the ball heading test (Nurhasan, in Huda, 2012: 73). The sampling technique uses purposive sampling with the following criteria: (1) Sampling must be based on certain characteristics, which are the main characteristics of the population; (2) The subjects taken as samples are truly the subjects that contain the most characteristics found in the population. The research subjects used were male students of class VIII SMP Negeri 8 Watampone, which consisted of 20 students. Based on the results of the study, there was a significant effect of sit-up exercises on the results of heading soccer games in male students of class VIII SMP Negeri 8 Watampone, with a mean pre-test of 4.01, a mean post-test of 5.63, and a p value of 0.017 < 0.05. There was a significant effect of squat jump training on the results of heading soccer games in male students of class VIII SMP Negeri 8 Watampone, with a mean pre-test of 3.73, a mean post-test of 4.61, and a p value of 0.014 <0.05. Sit-up exercises are more effective than squat jump exercises for the results of heading soccer games in male students of class VIII SMP Negeri 8 Watampone, with a post-test difference of 1.015. Sit-up exercises are more effective than squat jump exercises, according to the results of heading football games in male students of class VIII SMP Negeri 8 Watampone, with a post-test difference of 1.015.